Sexual relationships between athletes and coaches: Love, sexual consent, and abuse - Johansson, S. (Avhandlingsserie för Gymnastik- och idrottshögskolan, 09, 2017)
Coach-athlete sexual relationships (CASR) and sexual harassment and abuse (SHA) in sport can profoundly impact athletes` welfare and performance. Yet, it is often ignored due to sensitivity, secrecy, and lack of knowledge. There is no previous research on SHA in sport in Sweden, and legal, consensual, same-sex CASR is under-researched. The overall purpose of this doctoral thesis is to examine CASR in competitive sport in Sweden. More specifically: a) athletes` experiences of CASR; b) prevalence of SHA in coach-athlete relationships; c) conceptual and theoretical issues to broaden the understanding of CASR and SHA, will be examined.